DISCOURSE TOWARD STUDENTS WHO HATE MATHEMATICS IN SOLVING A MATHEMATICAL PROBLEM: AN ETHNOMATHEMATICAL PERSPECTIVE - Putra, Mulia (Jurnal Numeracy, 2024)
This research aims to identify students who hate mathematics in solving mathematical problem where culture is the context. In this research the context was Rumoh Aceh. By collecting data through various sources such as interview transcription and documentation, qualitative method is appropriate to describe how students who hate mathematics solve the mathematical problem. Students who hate mathematics, they hate mathematics is not simply because mathematics is difficult for them, rather their awareness toward mathematics itself. Roughly speaking, what they consider as not mathematics is mathematics. From several respondent who involve in this research, all of them have their own way in solving mathematical problem. In other way, all students who hate mathematics can solving mathematical problem, even all the answer is not match with the real needs of an Utoh. Utoh is a professional worker who expert in counting the total weaved rumbia leaves to cover whole roof of Rumoh Aceh. Students who consider mathematics as their enemy which means they hate mathematics cannot be said that they cannot solve mathematical problem at all, but they have the strategy to solve it, although they face some problem in the process of solving it. All of students’ answer called as alternative solution for solving mathematical problems. Finally in this research, students who hate mathematics has a good ability in making the representation of mathematical expression and this is a good information for teachers and researchers who conduct learning and research in mathematics at school.